Microbial communities variation analysis of denitrifying bacteria immobilized particles. (December 2019) - Hou, Liangang; Li, Jun; Liu, Yang
Graphical abstract: Highlights: New insights of microbial communities variation for the application of microbial immobilization technology. Immobilized denitrifying bacteria particles have achieved good denitrification effect on practical municipal wastewater. High-throughput sequencing shows the community structure changes in immobilized particles during the operation process. Abstract: The aim of this study was to investigate the denitrification performance and analyze the variation of microbial communities in immobilized particles which used in real municipal wastewater treatment. The bioreactor has achieved good denitrification effect on real municipal wastewater treatment, the NO3 − -N and TN removal efficiencies reached 77.4% and 68.3%, respectively. High-throughput sequencing shows that the community structure and relative abundance of bacteria changed greatly, especially at the phyla and genes levels in immobilized particles. Through the investigation of this paper, we think the influence of microflora variation should be considered when using microbial immobilized technology for wastewater treatment, and we suggest that immobilized particles cannot be used indefinitely and it needs to be replaced periodically.